RIGHTS AND DUTIES OF TEACHER AND STUDENT (IN THE LIGHT OF SEERAH OF THE HOLY PROPHETﷺ): معلم و متعلم کے حقوق و فرائض (سیرتِ نبی ﷺ کی روشنی میں ) - Somia Begum, Dr. Naseem Akhter, Dr Syed Muhammad Nasim Sarwer (International Research Journal of Arabic and Islamic Studies, 2021)
Education is a source whose purpose good character of man and is his teachings. Knowledge is like a light who takes the righteous man to the destination which is not only of the worldly life rather the guarantor of end life too. That’s why education and training is the style prophet hood. Teacher and learner (student) are the two necessary parts/pieces. The responsibility of teacher is not only to teach learner (student) but also to educate him. Islam is very much convinced about importance of the teacher and scholar even in the holly Quran Majeed the first blessing was awarded to knowledge of education. As the preliminary “Wahi” was revealed in our prophet Muhammad (PBUH) so the importance and VERTURE of knowledge was explained which is given herein made a statement verbatim:-